Awareness and utilization of Papanicoloau smear among health care workers in Maiduguri, Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Cervical cancer is the leading cause of cancer related deaths among women in developing countries. Lack of awareness and comprehensive cervical cancer screening programmes offered in most developing countries are partly responsible for the high burden of disease. In developed countries, routine use of Papanicoloau smear, in part, has led to a decline in cervical cancer incidence and mortality.Objective:To determine the level of awareness, utilisation and factors associated with awareness of Pap smear test as a tool for cervical cancer screening among health care workers (HCW) in Maiduguri north-eastern part of Nigeria.Subjects and Methods:This was a cross-sectional questionnaire based study conducted among 150 health care workers in Maiduguri, between January and March 2010. Simple descriptive statistics was employed in the analysis of data.Results:A total of 150 participants were recruited for the study. The majority (141) of respondents were aware of Papanicolaou smear and 23.3% of the female respondents had done the test previously. Majority (90.8%) of the men were willing to pay for their spouses to do the screening; some of them (20.0%) were indifferent if their spouses perform the cervical screening without their consent. The major reason given for carrying out the test was for prevention of the disease. The major source of information was the hospital (84.7%). Majority of the women were willing to do the test if offered the opportunity either free (70.6%) or with payment (29.4%). A number of socio-demographic variables played crucial roles in awareness and utilisation of Pap smear. These included higher level of educational status (P= 0.000) of the respondents, increased maternal age (P= 0.001) and high parity (P= 0.003).Conclusion:There is poor utilisation of Pap smear among HCW despite high level of awareness and availability of screening services. A number of socio-demographic variables play crucial roles in awareness of Pap smear. The reasons for the low utilisation among health care workers, who are the custodians of health care need to be investigated to improve their utilisation of Pap smear.